The use of operational harmful algal bloom monitoring systems in South Africa to assess long term changes to bloom occurrence & impacts for aquaculture - Mtetandaba, Aphiwe (Department of Oceanography, 2021)
The south coast of South Africa is a very dynamic, productive, high energy environment and is considered to be a generally challenging setting for in-water aquaculture. One of the largest environmental threats to aquaculture are harmful algal blooms (HABs), a natural ecological phenomenon often accompanied by severe impacts on coastal resources and local economies. There is a wide variety of potentially harmful blooming species in the region, with impacts resulting from both toxicity and the negative effects associated with high biomass. While HABs are fairly well documented around the southern Benguela area, the primary concern is the lack of long-term data showing if blooms are becoming more frequent, persistent or are having greater impact over the last decades, consistent with environmental change experienced in the region. For this study, high-resolution satellite remote sensing observations from 16 years of MODIS-Aqua (1 km) and one month of Sentinel-3 OLCI (300 m), using regionally optimised blended algorithms, were used to investigate the spatial distribution and temporal variability of chlorophyll-a (Chl-a) along the south coast of South Africa. A Chl-a threshold of 27 mg m−3 was used as an analytic to identify the occurrence of high biomass blooms in the remote sensing data. Phytoplankton count data from aquaculture farms are used to provide information corresponding to changes in phytoplankton community structure, and to investigate the distribution and seasonal trends of HABs along the south coast. To further explore the spatial and temporal distribution, phytoplankton species considered harmful for this study were identified and classified to their seasonal occurrence: some species were consistently present throughout the years, however each region showed contrasting seasonality. A second interest of this study is linked to assessing the capacity of the aquaculture industry to make profitable use of existing observational and early warning tools. The impact of HABs on the environment or in aquaculture facilities can be potentially mitigated by increasing the industry awareness and early warnings of HAB development. In this regard, the Fisheries and Aquaculture Decision Support Tool (DeST) was used in order to develop short term alerts on HAB development. The EO analyses conducted here specifically use the same methods used by this DeST to demonstrate the use of this tool for historical analysis in addition to real time alerting. In order to evaluate the effectiveness of the tool and how the aquaculture farmers use the ABSTRACT information provided on the DeST, an online user feedback was generated, and distributed to all stakeholders via email